OPPORTUNITIES AND CHALLENGES FOR TOURISM MANAGEMENT BY THE GOVERNMENT - Istiharah; Novia Irianti, Nana; Shabirin Shaddiq, Muhammad; Rizka Milania Ulfah , Baiq (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
Indonesia’s tourism sector holds significant economic and cultural potential, contributing 4.5% to the national GDP in 2022 while supporting millions of jobs. However, the industry faces pressing challenges, including environmental degradation, social inequities, and uneven resource distribution. This study examines the roles of governance and technology in addressing these issues, proposing strategies to enhance sustainability, equity, and resilience in tourism management. By leveraging collaborative governance and smart tourism technologies, the research highlights actionable pathways for inclusive growth. Recommendations emphasize fostering community-based tourism, advancing environmental policies, and bridging the digital divide. These findings provide a comprehensive framework for future policy initiatives and underscore Indonesia’s potential as a global leader in sustainable tourism development.